O gótico familiar de William Faulkner e Lúcio Cardoso: formas e dinâmica da opressão - Rogério Lobo Sáber (2020)
The literary Gothic consolidates its position as an aesthetical project that, since its origin back in the 18th century, stages and explores cultural anxieties and interdicts, mainly those installed within the familiar boundaries. This dissertation examines how the novelists William Faulkner (1897-1962) and Lúcio Cardoso bring the formal and thematic inventory of Gothic literature up to date in their works Absalom, Absalom! (1936) and Chronicle of the murdered house (1959). The writers denounce points of familiar vulnerability that, once attacked, culminate in the shattering of orders attached to tradition. Among all the Gothic types and themes that the novelists reshape, we grant a central role to the hero-villain and to the literary motive of revenge. We claim that Thomas Sutpen and Demétrio Meneses are the hero-villains in charge of distorting the familiar context into a claustrophobic perimeter marked by oppression, examined in its dynamics and multiple forms. Supported by a realistic representational pact, the books stage multiple forms of factual and symbolic violence, denounced as resounding vortices of destruction and legitimated by the cultural discourse.